The Institutionalist Theory of the Business Enterprise: Past, Present, and Future. Issue 3 (3rd July 2019) - Jo, Tae-Hee
Abstract: This article examines the historical developments of the institutionalist theory of the business enterprise since the early 1900s in order to demonstrate its distinctive characteristics that are often overlooked or belittled by some institutional-evolutionary economists and most mainstream economists. I argue that the institutionalist theory is an evolving and emergent theory, which bears a reciprocal, evolutionary, and cumulative relationship between the business enterprise and society. The institutionalist theory is, therefore, suitable for the understanding of the real-world business enterprise as it can be modified and refined along with the evolution of capitalism. The article begins with a discussion of the present state of the institutionalist theory. The following section is devoted to the major contributions to the institutionalist theory situated in the evolution of U.S. capitalism. The penultimate section provides a critical discussion of new institutional and evolutionary approaches to the firm. The article concludes with a brief discussion as to what should be done for the further development of the institutionalist theory of the business enterprise.